Inventory Control of Main Distribution Material (MDU) PB PD 1 Phase at PT PLN UP3 Banten Selatan - Rahmaddial, Andre; Suparno, Suparno (Journal Research of Social Science, Economics, and Management, 2025)
PT PLN UP3 Banten Selatan faces material shortages that delay customer connections, impacting service quality and regulatory compliance. This study aims to optimize inventory control for Main Distribution Unit (MDU) materials, focusing on 1-phase New Installation (PB) and Capacity Upgrade (PD) requests. The research compares current inventory practices with continuous review (s,S) and periodic review (R,s,S) systems to identify optimal inventory parameters. Risk management is addressed using the Multi-Criteria Decision Making (MCDM) framework, specifically the Analytical Hierarchy Process (AHP), to prioritize and mitigate risks in inventory control. Data from PLN’s Executive Information System (EIS)—including demand history, material BoQ, and procurement costs—were analyzed to calculate inventory parameters for each method. The AHP method, supported by expert input, was used to weigh and rank risk criteria and subcriteria. Results show the continuous review system achieves a 100% service level and reduces costs, saving Rp 738,736,538 compared to the periodic review method. Financial risk emerged as the top priority, followed by supply and demand risks. Eight high-risk subcriteria were identified, such as rising storage costs and inaccurate demand forecasts. Proposed mitigation strategies include strict budget planning and vendor diversification. This study provides actionable recommendations for PLN to enhance inventory efficiency, reduce financial risks, and improve service delivery, while also contributing to academic literature on inventory control and risk management in the utility sector.